Human factors considerations for ultrasound induced mid-air haptic feedback - Khan, James (2022)
The engineering design process can be complex and often involves reiteration of design activities in order to improve outcomes. Traditionally, the design process consists of many physical elements, for example, clay/foam modelling and more recently Additive Manufacturing (AM), with an iterative cycle of user testing of these physical prototypes. The time associated with creating physical prototypes can lengthen the time it takes to develop one product, and thus, comes at a burdensome financial and labour cost. Due to the aforementioned constraints of the conventional design process, more research is being conducted into applications of Virtual Reality (VR) to complement stages of the design process that would otherwise take and cost a significant amount of time and money. VR enables users to create 3D virtual designs and prototypes for evaluation, thus facilitating the rapid correction of design and usability issues. However, VR is not without its pitfalls, for example, it often only facilitates an audio-visual simulation, thus hindering evaluation of the tactile element of design, which is critical to the success of many products.